Five new species of the flesh fly genus Boettcheria (Diptera: Sarcophagidae) - Rosenmejer, Trine; Pape, Thomas (Zootaxa, 2018)
Five new Neotropical species of the flesh fly genus Boettcheria Parker, 1914 are described: B. brachion sp. nov. (Venezuela), B. dikros sp. nov. (Costa Rica), B. hirta sp. nov. (Costa Rica), B. tridens sp. nov. (Venezuela), and B. ulo sp. nov. (Venezuela). The definition of the genus is briefly discussed.